Detection of Brucella antibodies of sheep and goats by using two serological tests in Al-Sulaimanya governorate: Osman M. Jabary and Ikram A. Al-Samarraee - Jabary, Osman M. (The Iraqi Journal of Veterinary Medicine, 2015)
A research was carried out to detect Brucella antibodies of sheep and goats in Al-Sulaimanya governorate by using modified Rose Bengal test and indirect ELISA. A total of three hundred and eleven (311) whole blood samples (160 sheep and 151 goats) were collected randomly from eight different regions in Al-Sulaimanya governorate from unvaccinated flock with different ages. A total percentages of positive result by using modified Rose Bengal test was 14.46% (20% in sheep and 8.6% in goats), while by using indirect ELISA was 27.6% (35.2% in sheep and 19.2% in goats) with significant (P<0.05) differences. It revealed that rates to modified Rose Bengal test were 14.34% in female and 10.09% in males while to indirect ELISA 26.35% in female and 33.9% in males in sheep and goats, In conclusion of this study the high seroprevelence was at 1-3 years 19.2% and ˃3 years 33.96% according to modified Rose Bengal test and indirect ELISA, respectively.